CONSUMER ATTITUDE AND INTENTION TO ADOPT MOBILE WALLETS IN INDIA - JAYESH, G.S. (International Journal of Psychosocial Rehabilitation, 2018)
In today – world, smart phone has become an essential part of one’s daily life. Mobile users can nowadays use their Smartphones to make money transactions or payments by using applications installed in the phone. When smartphones can function as leather wallets, it is called “Digital Wallet” or widely known as “Mobile Wallet”. The main aim of this empirical study is to examine the mobile wallets usage Consumer attitude and intention to adopt mobile wallet in Chennai city, India. The respondents were categorized on the basis of gender, age and occupation. The study is based on the primary data collected from 481 respondents by using a structured questionnaire. Five point likert scales was used in questionnaire for obtaining responses. The statistical tools applied in this study are ANOVA, Chi Square, Friedman Test, and frequency analysis. SPSS 20 was used to perform statistical analysis.